Political Ideology and Indonesian Translation of the Qur'an - Naufal Hidayatullah; Moh. Abdul Kholiq Hasan; Ainur Rhain; Kharis Nugroho (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines political ideology in Indonesian translations of the Qur'an. This study aims to analyze differences in word choice in the Qur'an that explain how political verses of the Qur'an are translated and interpreted in social, historical, and political contexts. Using a qualitative method based on literature study, this study examines the translations of the Ministry of Religious Affairs (2002 and 2019) and the Tafsir Al-Qur'anul Karim by Muhammad Yunus, focusing on verses related to politics. Linguistic-semantic and ideological analyses indicate significant differences that have implications for the nuances of meaning and political orientation. This study also identifies three ideological tendencies in understanding politics, including: traditionalist-authoritarian, revivalist-transformative, and modernist-contextual, which influence the reconstruction of the meaning of verses in translations. These findings confirm that translations of the Qur'an are not merely linguistic products, but ideological spaces influenced by the translator's social, political, and religious paradigms.